Microbial priming elicits improved plant growth promotion and nutrient uptake in pea. Issue 3 (2nd July 2016) - Verma, Shikha; Adak, Anurup; Prasanna, Radha; Dhar, Shri; Choudhary, Harshwardhan; Nain, Lata; Shivay, Yashbir Singh
Abstract : Legume–microbial interactions focus mainly on Rhizobium . The present study aimed to evaluate the plant growth-promoting (PGP) potential of bacterial and cyanobacterial formulations and variety-specific differences following their inoculation in two varieties of pea ( Pisum sativum L.), namely Arkel and GP-17. Providencia sp. PW5– Anabaena laxa CW1 treatment was the most promising, with an 11%–76% increase in defense enzyme activity in both varieties. Interestingly, Arkel responded better in terms of nitrogenase activity, which was enhanced several-fold in the inoculated treatments, and exhibited a significant correlation ( r = 0.787, 0.778, 0.755; p < 0.05) with shoot length, fresh weight and nodule number per plant, respectively. Nodule number was significantly correlated ( r = 0.74, 0.81; p < 0.05) with PAL and PPO activity, respectively, and with microbial biomass carbon, alkaline phosphatase and dehydrogenase activity ( r = 0.582, 0.538, 0.666; p < 0.05), respectively. Variety GP-17, however, responded better in terms of increasing the polysaccharide and glomalin content of soil. This study reveals the promise of co-inoculation of PGPRs (plant growth-promoting Rhizobacteria) as synergistic partners for improving plant growth mobilization of major nutrients in pea. However, there is a need to study root exudate patterns to identify promising microbe–variety combinations.